Problematika Penundaan Pemilihan Umum 2024 - Ikbal Tawakal; Tri Susilowati (Universitas Sains dan Teknologi Komputer, 2024)
In this democratic country, elections are the main aspect to be held continuously. Through this election process, we as citizens can participate directly in the process of sovereignty. The postponement of the election has hampered the participation of the people in carrying out the sovereignty process. The purpose of this study is to find out how the impact caused by the postponement of elections and the extension of the term of office of the president and vice president for the State. This research is normative law research, which is a legal research that examines laws that are conceptualized as norms or rules that apply in society, and become a reference for everyone's behavior. The results of this study clearly state that elections are held every five years and the positions of the president and vice president are only a maximum of two terms of office which are clearly stated in the 1945 Constitution. The impact of postponing elections is unconstitutional which is a form of betrayal of the constitution and abolishes the spirit of reform as outlined in the amendments to the 1945 Constitution.